2022
DOI: 10.1038/s41598-022-20497-w
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of endothelins in neuroprotection of valosin-containing protein modulators against retinal ganglion cell damage

Abstract: We have previously shown that Kyoto University Substances (KUSs), valosin-containing protein (VCP) modulators, suppress cell death in retinal ganglion cells of glaucoma mouse models through alterations of various genes expressions. In this study, among the genes whose expression in retinal ganglion cells was altered by KUS treatment in the N-methyl-d-aspartic acid (NMDA) injury model, we focused on two genes, endothelin-1 (Edn1) and endothelin receptor type B (Ednrb), whose expression was up-regulated by NMDA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Rg1 has been found to have protective effects on various tissues and organs in the human body, with anti-apoptotic, anti-inflammatory and anti-aging effects. Previous studies have shown that Rg1 exerts various pharmacological effects through various mechanisms such as inhibition of apoptosis-related protein levels, downregulation of inflammatory mediators and anti-oxidation, effectively exerting organ-protective effects against I/R induced damage [9][10] . Some studies have reported that Rg1 can reduce the release of reactive oxygen stress and lactate dehydrogenase in a hypoxia-reperfusion model of cardiomyocytes, thereby improving the ability of cardiomyocytes to resist I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Rg1 has been found to have protective effects on various tissues and organs in the human body, with anti-apoptotic, anti-inflammatory and anti-aging effects. Previous studies have shown that Rg1 exerts various pharmacological effects through various mechanisms such as inhibition of apoptosis-related protein levels, downregulation of inflammatory mediators and anti-oxidation, effectively exerting organ-protective effects against I/R induced damage [9][10] . Some studies have reported that Rg1 can reduce the release of reactive oxygen stress and lactate dehydrogenase in a hypoxia-reperfusion model of cardiomyocytes, thereby improving the ability of cardiomyocytes to resist I/R injury.…”
Section: Introductionmentioning
confidence: 99%